POTENSI ANIMASI DALAM USAHA MENAMBAH DAYA TARIK MASYARAKAT TERHADAP CERITA DAERAH DI INDONESIA - Putra, Gede Lingga Ananta Kusuma; Novita, Sherly Agatha Surya (Anima Rupa, 2025)
As time progresses, Indonesian society's fascination with regional stories is decreasing. Many Indonesian people think that regional stories are old dated and uninteresting. Many ways have been taken to increase Indonesian people's interest in regional stories, one of which is using animation as an effort to increase public appeal. Animation itself in Indonesia has begun to be widely used in various fields, starting from advertising, social media, to films. The development of animation in Indonesia provides a great opportunity to attract public interest in regional stories. By using animation, it is hoped that it can increase people's interest in regional stories.